Special swimming instruction for the multiple handicapped - Vis, W. P. M. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
The human being can be looked upon as a moving object in space who finds himself between and in relation to the other objects and the environment. This can be called a fundamental aspect of human existence. In this context the swimming instruction must be considered a part of movement education and must be looked at in relation to the pedagogical and agogical perspective. This implies that we regard our pupils as persons who are disturbed or retarded in their total development and who need our special help in order to grow up a.Tld achieve optimal human functioning. This assistance that is directed toward the individual pupil may be referred to as education. If this educational assistance has as its starting point the moving person, we refer to it as movement education. Through conscious influence of the movement behavior of the student, movement education provides an important contribution to total education. This form of education is fundamentally important, since human movement means contact with the environment and confrontations and actions with persons and objects. These moving, manipulating, exploring actions give the pupil an experience and a notion of the qualities a.nd properties of persons and objects: balls are round things with which you can roll, very near and far away, that's only matter of distance one has to cover; high and low is a matter of climbing and falling; light and heavy is a matter of lifting up and carrying away; etc. Moreover, while moving, a pupil experiences and unfolds his ovm possibilities, and we hope he'll come to enjoy them; while doing he comes to a notion of himself as somebody who is able or unable to do particular things. This forms among others a base for the achievement of self-consciousness. All this means development, characterized by progress, unfolding, differentiation and integration, in which "moving" plays an essential part. Generally the mentally retarded can only develop himself through actual moving among objects and persons; he can't argue or discuss things. He gets to know his world by dealing with it actively, by moving; movement is-certainly for mental retardates a necessity for development. Herewith, we have given the motive for an essential aspect of the total education with regard to individuals who are characterized as developmentally disturbed pupils.